2009
DOI: 10.1002/anie.200900437
|View full text |Cite
|
Sign up to set email alerts
|

From Metal Binding to Nanoparticle Formation: Monitoring Biomimetic Iron Oxide Synthesis within Protein Cages using Mass Spectrometry

Abstract: Mass measurements of metal-mineralized protein cages allowed quantitative examination of the effects of metal-ion concentration on the final nanoparticle size. Modeling using a kinetic master equation suggests that particle growth involves both a binding phase and a growth phase (see picture; I: relative abundance; LiDps: a DNA binding protein; (n)Fe: number of Fe atoms).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
(25 reference statements)
0
26
0
2
Order By: Relevance
“…Therefore, the Dps –encapsulated nanoparticles including Co(O)OH and Co 3 O 4 [66], γ-Fe 2 O 3 [67, 68], CdS[69] and Pt[70] have been synthesized using conceptually the same approach as that of ferritins. However, the resulting-nanoparticles are extremely small as Dps proteins have smaller interior cavity of 5nm than that of 8nm in ferritins.…”
Section: Biomedical Technological and Catalytic Applications Of Ferrmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the Dps –encapsulated nanoparticles including Co(O)OH and Co 3 O 4 [66], γ-Fe 2 O 3 [67, 68], CdS[69] and Pt[70] have been synthesized using conceptually the same approach as that of ferritins. However, the resulting-nanoparticles are extremely small as Dps proteins have smaller interior cavity of 5nm than that of 8nm in ferritins.…”
Section: Biomedical Technological and Catalytic Applications Of Ferrmentioning
confidence: 99%
“…In addition to protein only macromolecular complexes, it has been demonstrated that interactions between protein macromolecules and metal ions or nanoclusters can be preserved, allowing metal deposition to be monitored by tracking mass increases. [68, 70] Mass spectrometry has sufficient mass accuracy and resolution to discriminate two to three metal ions depending on the atomic masses of metal ions. Therefore, it is possible to concurrently detect multiple populations distributed within an ensemble and monitor their changes individually instead of averaging over all signals.…”
Section: Nanoparticle Assembly (Growth) Protein Cage Assembly and Jamentioning
confidence: 99%
“…In addition, properties such as magnetic response or bandgap energy are often dependent on the crystalline domain size of a sample. In protein-templated nanoparticle synthesis, the size of nanoparticles can often be controlled by tuning the metal ion/protein cage ratio – this results in a fairly narrow distribution of sizes with a mean value that can be easily controlled during synthesis 19 . The feasibility of technological applications of protein-templated nanoparticles will depend largely on our ability to exert synthetic control over material properties beyond the average particle size, such as the typical crystalline domain size within a nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…Weiterhin wurde die Struktur der beiden Intermediate mit IMMS ermittelt, sowohl von den intakten als auch von den CID-fragmentierten Spezies. [181] Beide [183][184][185] Dendrimere, die kovalent an die Innenseite eines Proteinkäfigs gebunden sind, kçnnen zu nachfolgenden Generationen herangezogen werden. Dabei kçnnen die Partikel ihre Stabilität erhçhen und damit eine Anwendung unter extremeren Bedingungen ermçglichen.…”
Section: Massenanalyse Von Intakten Viralen Aggregatenunclassified